The "Quartiere game" (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
It is the academic year 1985-86: a discussion is being held on the teaching approach to adopt for Design in the first years of the Architecture programme; some reckon we should just continue to pursue the basic rules of Composition, while others think teaching should involve an open debate with the real world of building and city planning. These are the years when the topic of complexity, in situations and in decision-making processes, was gaining a foothold, a topic which was part of the general feeling of disorientation that typified the academic world at the time, uncertain whether to continue following the post-1968 path of "innovation", or to go back to a somewhat unlikely form of "restoration".Those who held that, from a strictly didactic viewpoint, the most effective teaching approach was that of full-immersion, rather than a graded step-by-step learning process, from the simpler and more elementary ideas to the more difficult and/or more specialised, were bound to opt for a confrontational approach and first-hand experimentation. For anyone determined to pursue this choice, why not try out a method whose area of application was where complexity reigned in initial conditions of uncertainty? Why not see if the method of gaming simulation would work with regard to design; it had recently been applied to fields like economic planning, but why should it not also be beneficial to the domain of knowledge and the imagination?